Workplace health training: a theoretical and empirical model - Drake, Travis, author; Kraiger, Kurt, advisor; Gibbons, Alyssa, advisor; Graham, Dan, committee member; Sarason, Yolanda, committee member (Colorado State University. Libraries, 2017)
For the current study I proposed a complete, integrated model of workplace health training including its antecedents, structure, and outcomes. Additionally, I proposed the concept of 'training enrichment', where different types of training would have a multiplicative effect on relevant work outcomes. Based on this proposed model, I empirically tested the longitudinal effects of workplace health training on employee attitudes, employee performance ratings, and learning culture. I hypothesized that: 1) the structure of my empirical model would fit the data, 2) workplace health training would positively impact employee attitudes and employee performance, 3) a strong learning culture would lead to increased employee participation in workplace health training, and 4) workplace health training would interact with leadership training to positively impact employee attitudes and employee performance. Results from the structural equation model and associated statistical tests showed that while the structure of the model was appropriate, the longitudinal effects of the training were minimal. Overall, this study provides a strong foundation for structuring workplace health training, as well as some evidence of its longitudinal effectiveness.
Keywords: health; leadership; training; interaction; enrichment; longitudinal